MODEL REGRESI NONPARAMETRIK ADITIF DENGAN FUNGSI LINK - Nasfirah, Siti; Budiantara, I Nyoman; Fitriasari, Kartika (MATEMATIKA, 2006)
﻿﻿If given a couple of data and the relationship between variable x and y is revealed as nonparametric regression model with is an error which is random variable with zero mean and variance and is unknown function. If is an additive function with x Rd, d ≥ 2. By using link function F, this research is focused on the way to get the estimator in additive component with link function by using two-stage methode and completed with simulation using logit link function. The result shows that two-stage estimator is eisier be used to model nonparametric regression by link function rather than Nadaraya-Watson and local linear. From the simulation, it’s obtained that of the mean and R2 value of the estimator is similar.